Renal Denervation Therapy in a Resistant Hypertensive Patient-Report of First Case in Bangladesh - Ali, M; Momen, A; Karmakar, PK; Patwary, MSR; Haque, MA; Goni, MN; Islam, AKMM; Huda, RM; Rahman, A; Majumder, AAS (Cardiovascular Journal, 2012)
Not available DOI: http://dx.doi.org/10.3329/cardio.v5i1.12282 Cardiovasc. j. 2012; 5(1): 112-119